Respuesta :

iGreen
We can use the substitution method to solve this problem.

The second equation is [tex]\sf y=2x[/tex], so we can plug in 2x for 'y' in the first equation:

[tex]\sf 5x-2y=3[/tex]

[tex]\sf 5x-2(2x)=3[/tex]

Multiply:

[tex]\sf 5x-4x=3[/tex]

Combine like terms:

[tex]\sf x=3[/tex]

This is the x-value of our solution, we can plug this into any of the two equations to find the y-value:

[tex]\sf y=2x[/tex]

[tex]\sf y=2(3)[/tex]

Multiply:

[tex]\sf y=6[/tex]

This is the y-value of our solution. So our entire solution is (3, 6).